Empowering Local Workers To Resolve Social Conflicts In West Aceh District’s Palm Oil Sector - Jamaluddin; Marlia Sastro; Ramziati; Yusrizal; Sela Azkia; Yahya, Azhari (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This study starts with the existence of social conflict and the importance of resolving social conflict between oil palm plantation companies through the empowerment of local workers. For the sustainability of the oil palm plantation business and improving people’s welfare. Article 74 paragraph (2) of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and Article 2, paragraph (1) letter e of Law Number 19 of 2003 concerning State-Owned Enterprises. Although efforts to resolve the conflict between the community and oil palm plantation companies in West Aceh have been made, the conflict has not been resolved until now. This study aims to analyze the obstacles to resolving social conflict between the community and oil palm plantation companies in West Aceh. This study uses a sociological legal approach to look more deeply at the effectiveness of law in society. The study uses primary data and secondary data as well as field data in West Aceh. The results of the study indicate that the obstacles to resolving the conflict between the community and oil palm plantation companies in West Aceh are because many productive-age villagers are not working and the empowerment program is not running effectively. This study produces a model for empowering local workers through CSR budgets to provide job training to productive age people aged 18-35 years so that productive age people have skills that can encourage them to live independently and improve their quality of life.